'I may destroy you': why media representations of sexual violence matter - Mishra, Ankita; House, Melody; Asser, Zoe; Beddows, Amy (Policy Press, 2022)
The Media Sigils are part of the Violence Against Women and Girls Research Network (VAWGRN). We are a group of PhD students with a shared interest in media representation of violence against women. In April, we held our first event: a panel discussion on Michaela Coel’s riveting drama ‘I May Destroy You’.